2014
DOI: 10.1186/1471-2334-14-129
|View full text |Cite
|
Sign up to set email alerts
|

Is elevated Red cell distribution width a prognostic predictor in adult patients with community acquired Pneumonia?

Abstract: BackgroundCommunity acquired pneumonia (CAP) is a major cause of morbidity and mortality. We recently demonstrated that among young patients (<60 years old) with CAP, elevated red blood cell distribution width (RDW) level on admission was associated with significant higher rates of mortality and severe morbidity. We aimed to investigate the prognostic predictive value of RDW among CAP patients in general population of internal wards.MethodsThe cohort included patients of 18 years old or older who were diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 25 publications
3
32
1
6
Order By: Relevance
“…The adjusted OR rose from1.12 to 1.40. RDW was reported as a binary variable in 2 studies [28, 33], and we found that the increased RDW levels were associated with a higher risk of death (OR, 2.12; 95%CI, 1.82–2.46) with low heterogeneity ( I 2 = 0, P = 0.49). And 4 studies provided data on AUC from 0.63 to 0.76 of RDW in prediction mortality [23, 25, 31, 33].…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The adjusted OR rose from1.12 to 1.40. RDW was reported as a binary variable in 2 studies [28, 33], and we found that the increased RDW levels were associated with a higher risk of death (OR, 2.12; 95%CI, 1.82–2.46) with low heterogeneity ( I 2 = 0, P = 0.49). And 4 studies provided data on AUC from 0.63 to 0.76 of RDW in prediction mortality [23, 25, 31, 33].…”
Section: Resultsmentioning
confidence: 85%
“…In addition, because of the studies by Purtle et al and Bazick et al were conducted in the same hospitals and derived from the same study periods [2, 12] and the risk of data duplication was inevitable, thus the study by Purtle et al was excluded [12]. A similar situation also occurred in the studies by Braun et al [26, 28], and his early study was excluded [26]. There was no additional studies were obtained through reviewing the bibliographies of relevant reviews or systematic reviews and there was no discrepancy between two reviewers.…”
Section: Resultsmentioning
confidence: 99%
“…(8) In one study done by Eyal Braun et al in 2014, where 3815 patients of community acquired pneumonia were studied, they found 16.9% (32.69% in our study) mortality in patients with RDW <=15% and 21.7% (59.18% in our study) mortality in patients with RDW >15%. (9) In another study done by Nader A Mahmood et al in 2014 RDW ≥16% was independently associated with an APACHE II score of ≥15. This suggests that septic patients with an RDW ≥16% may have a higher severity of illness.…”
Section: Discussionmentioning
confidence: 92%
“…Specifically, it is associated with high rate of morbidity and mortality in the case of patients with chronic heart failure [22, 23, 24]. Likewise, it is a marker of poor prognosis for patients with infectious diseases [25, 26]. However, there are relatively few reports focusing on RDW in the area of oncology.…”
Section: Discussionmentioning
confidence: 99%